PROBLEMS OF DIAGNOSIS OF COMMUNITY ACQUISITED PNEUMONIA IN YOUNG CHILDREN - Ibragimova Nadiya Sabirovna; Irmamatova Fotima (TADQIQOTLAR.UZ, 2024)
Annotation. The most common form of acute infectious pneumonia in children is community-acquired pneumonia, which can be accompanied by the development of both pulmonary and extrapulmonary complications. The relevance lies in the complexity of diagnosis and treatment of community-acquired pneumonia in children. 96% of all deaths due to pneumonia occur in early childhood, and the maximum number of adverse outcomes occurs during infancy. The article provides data on pneumonia as one of the most common and serious lung diseases in children.